Differences in Knowledge About Dental Caries Using a Modified Monopoly Game as Educational Media (Study at UPT SDN 1 Gresik in Grade 4 Students) - Nadita, Nahdya; Larasati, Ratih; Putri, I Gusti Ayu Kusuma Astuti Ngurah (SURABAYA DENTAL THERAPIST JOURNAL, 2026)
Dental caries is a common dental health problem among children worldwide, including in Indonesia. Dental caries causes teeth to become porous, have cavities, and break, resulting in suboptimal growth. Based on the results of an initial dental examination of fourth-grade students at the UPT SDN 1 Gresik, 23 students (85.18%) had dental caries, and four (14.81%) were caries-free. The Indonesian Dental Association (SKI) handbook lists the prevalence of dental caries among Indonesians aged 10-14 as 63.8%, with the proportion of caries-free children at the same age as 35.5%. This study aimed to determine the knowledge of fourth-grade students at UPT SDN 1 Gresik regarding basic dental caries, including the definition, signs, factors, causes, effects, treatment, and prevention. The study used an analytical study with a pre-experimental one-group pretest-posttest design. The sample consisted of 40 students from the UPT SDN 1 Gresik, aged 10-11 years, with 25 boys and 15 girls as genders. The instrument used in this study was a questionnaire to assess knowledge about dental caries. The data analysis technique used was the Wilcoxon test. The results of this study showed a Wilcoxon test (ρ value = 0.000 or <0.05), thus concluding that H0 was rejected, indicating a difference in knowledge about dental caries before and after the education using the modified Monopoly game.